HUKUM JUAL BELI AYAM TIREN DALAM FIQH MUAMALAT - Al Hafidz Ibnu Qayyim (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2020)
The Law of Buying and Selling Tiren Chicken in Muqalat Fiqh. The purpose of this study is to provide an explanation to the public regarding the law of buying and selling carcasses of tiren chicken according to the muamalat fiqh. Buying and selling carcasses of chicken chickens is forbidden if the purpose is to be consumed, but if it is for use other than for human consumption, such as fertilizer or for pet food such as cats and / or tigers, then the law may be noted that the government or the party that has the authority must closely monitor it. This is based on the Prophet's hadith. From Abdullah bin Abbas: Once passed in the presence of Rasulullah saw carcass of goat (to be thrown), then he asked: